The Impact of Divorce Cooling-Off Period on Registered Divorces: Evidence from China - Wenge Zheng; Bowen Niu; Zhenguo Chen (Social Sciences)
The divorce rate in China has continued to rise since the 21st century. In order to reduce impulsive divorces, the divorce cooling-off period (DCOP) system was established in the Civil Code of China. The aim of this research is to examine the impact of the DCOP on registered divorces. Data from the Ministry of Civil Affairs, National Bureau of Statistics, civil affairs departments, and statistical bureaus of 31 provinces, the 2018 to 2023 editions of the China Statistical Yearbook, and the China Civil Affairs Statistical Yearbook were utilized in this work. The event study analysis reveals that the number of registered divorces decreased significantly in China after the DCOP provision’s enforcement. The ordinary least squares model indicates an average annual decrease of about 2.6 million registered divorces when the DCOP provision takes effect, and the DCOP plays a decisive role in this decrease, which suggests that the DCOP system has achieved its original intention. This research not only highlights the important role of the DCOP in reducing registered divorces but also provides insights on how to improve the DCOP system and promote the stability of marriage.